Homogeneous high-curvature porous carbon nanofiber material and preparation method thereof
High-curvature porous carbon nanofiber materials were prepared by using a self-templating method and dual-temperature gradient calcination technology. This solved the complexity and residue problems caused by catalyst supports in traditional methods, and achieved efficient and low-cost preparation of carbon nanofibers, expanding their applications in energy storage, catalysis and biomedicine.
Patent Information
- Application Number
- CN202410560238.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-10-24
AI Technical Summary
Existing methods for preparing carbon nanofibers rely on catalyst supports, which increases the complexity of the preparation process and may result in catalyst residues, limiting their application range and performance.
By employing a self-templating method and providing a carbon source through gradient calcination in two temperature zones, in-situ growth of carbon nanofibers under carrier-free conditions is achieved, forming carbon nanofiber materials with high curvature and porous structure. This avoids the problem of catalyst residue, and the microstructure of the material can be precisely controlled by adjusting reaction conditions such as temperature, pressure, and gas flow rate.
High-curvature, porous carbon nanofiber materials with a fishbone crystal structure were prepared, exhibiting excellent performance and suitable for energy storage, catalysis and biomedicine, reducing production costs and expanding the scope of applications.
Smart Images

Figure HDA0004827475400000011 
Figure HDA0004827475400000021 
Figure HDA0004827475400000031
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of carbon material synthesis, in particular to a homogeneous high-curvature porous nanocarbon fiber material and an efficient carrier-free preparation method thereof. BACKGROUND
[0002] In the field of nanotechnology, nanocarbon fibers (CNFs) have attracted extensive attention due to their unique physical and chemical properties and wide application prospects. CNFs not only have the advantages of high strength and high modulus of traditional carbon fibers, but also exhibit great potential in the fields of electrochemical energy storage, catalysis, and biomedical engineering due to their nanoscale characteristics. CNFs can be prepared by various methods, including chemical vapor deposition (CVD), high-temperature spray pyrolysis, electrospinning pyrolysis, arc discharge, and radio frequency magnetron sputtering. CVD is one of the most commonly used methods for preparing CNFs. In the CVD process, carbon source gas (such as methane or ethylene) and carrier gas (such as hydrogen) are used in the presence of a suitable catalyst (such as iron, nickel, or cobalt) to grow CNFs on the surface of the catalyst through pyrolysis. By controlling the reaction conditions (such as temperature, pressure, and gas flow rate), the morphology, structure, and performance of CNFs can be adjusted.
[0003] However, existing CNFs preparation methods usually rely on the use of catalyst carriers, which not only increases the complexity of the preparation process but also may cause catalyst residue problems, limiting the application range and performance of CNFs. In view of the limitations of existing technologies, the present application proposes a new type of nanocarbon fiber material and its preparation method, aiming to solve the problems existing in traditional methods and further expand the application field of CNFs.
[0004] The nanocarbon fiber material of the present application has the characteristics of homogeneity, high curvature, and high porosity. These characteristics enable the material to maintain high strength and high electrical conductivity while also having excellent adsorption capacity and catalytic activity. In particular, the CNFs of the present application also have a "fishbone" crystal structure feature, which is formed by the accumulation of nanoscale graphite layers at different angles to the axial direction of the fiber, similar to the shape of a fishbone, thereby providing more active sites and enhancing the mechanical properties of the material.
[0005] In the preparation method of the present application, the precursor is directly decomposed under carrier-free conditions to form a porous carbon matrix. Subsequently, with the aid of the gas carbon source provided upstream, the in-situ growth of nanocarbon fibers is achieved by precisely controlling the reaction conditions such as temperature, pressure, and gas flow rate. This method not only avoids the problems brought by the use of traditional carriers, but also enables the introduction of high-curvature, porous structure, and "fishbone" crystallinity during the formation of nanocarbon fibers, thereby obtaining a new type of nanocarbon fiber material with excellent performance.
[0006] This homogeneous, high-curvature, high-porosity, and "fishbone" crystal structure nanocarbon fiber material, due to its unique structural characteristics, is expected to play an important role in many fields. For example, in the field of energy storage, its high specific surface area and porous structure help to improve the energy storage performance of electrode materials; in the field of catalysis, its rich active sites and high porosity help to improve the efficiency and selectivity of catalysts; in the field of biomedicine, its high curvature, softness and "fishbone" structure may help to combine well with biological tissues, providing new solutions for medical devices and drug delivery systems.
[0007] In summary, the nanocarbon fiber material and its preparation method of the present application not only have innovation in technology, but also have wide prospect and potential value in practical application. The CNFs prepared by this method are expected to promote the development of nanotechnology field and bring revolutionary changes to related industries. SUMMARY
[0008] The present application aims to provide a homogeneous high-curvature porous nanocarbon fiber material and its efficient carrier-free preparation technology. The present application can efficiently and batch produce a new type of nanocarbon fiber material with uniform diameter, high curvature and uniform nanometer porous structure (i.e. the overall material includes or is formed by a porous material of nanocarbon fibers with uniform diameter and high curvature, the porosity is the pores formed between the high-curvature, i.e. curved, fibers) by a self-template method, using a double-temperature-zone gradient calcination strategy to provide a carbon source. In this preparation process, when a non-gaseous carbon source is selected, the raw material first undergoes gasification at a low temperature zone to generate carbon precursors in a gaseous form. Subsequently, these gaseous precursors flow with the carrier gas to the high-temperature zone of the reaction furnace. Here, with the catalytic action of the nickel metal nanoparticles generated in situ by the decomposition of nickel salt, the gaseous precursors decompose and deposit on the surface of the nickel nanoparticles under high-temperature conditions, ultimately forming nanocarbon fibers with high curvature and "fishbone" crystal structure characteristics, and the nanocarbon fibers form a new type of nanocarbon fiber material with uniform nanometer porous structure. By this method, the growth process of nanocarbon fibers can be effectively controlled, thereby obtaining high-quality materials with desired microstructure and performance. In addition, this method can select various carbon sources, and has many advantages such as simple and convenient synthesis process, low production cost, high yield, etc.
[0009] The present application provides an efficient carrier-free preparation method of a homogeneous high-curvature porous nanocarbon fiber material, comprising the following steps:
[0010] S1, citric acid and nickel nitrate (solid) are mixed according to a certain concentration ratio to form an aqueous solution, which is fully stirred as a precursor solution;
[0011] S2, poly(methyl methacrylate) (PMMA) microsphere templates are completely immersed in the precursor solution of S1, and then subjected to suction filtration and drying to obtain a precursor; S3, the precursor is placed in a double-temperature-zone gradient calcination furnace, and the temperature of the low-temperature zone is controlled at 300-600°C, and the temperature of the high-temperature zone is controlled at 700-900°C, and the precursor is calcined at a flow rate of 0.1-1 mL / min to obtain a new type of nanocarbon fiber material with uniform diameter, high curvature and uniform nanometer porous structure;
[0012] S3, placing the precursor obtained in step S2 or / and its derivative calcined in inert atmosphere in high temperature zone, placing selected non-gaseous carbon source in low temperature zone, then under the protection of inert carrier gas, carbon source in low temperature zone is gasified and flows to high temperature zone with inert carrier gas, and is catalytically converted into nanocarbon fiber on the decomposition product of catalyst generated in situ in high temperature zone, and the target nanocarbon fiber material is obtained in high temperature zone after cooling to room temperature.
[0013] Further, the concentration of citric acid in the precursor solution is 0.5-2 mol / L –1 ; preferably, the concentration of citric acid in the precursor solution is 1.0 mol / L –1 .
[0014] Further, the concentration of nickel nitrate in the precursor solution is 0.5-3 mol / L –1 ; preferably, the concentration of nickel nitrate in the precursor solution is 2 mol / L –1 .
[0015] Further, the impregnation condition is that the impregnation time at room temperature should be no less than 4 hours; preferably, the impregnation condition is that the impregnation time at room temperature is 12 hours.
[0016] Further, the high temperature zone in step S3 is placed with: the precursor obtained in S2 or / and the derivative obtained by directly calcining the precursor obtained in S2 under inert atmosphere at 290-400℃.
[0017] Further, the calcination temperature in the high temperature zone in step S3 is not less than 380℃, preferably 450-1000℃, the heating rate of the high temperature zone is 1-50℃ / min –1 , preferably 10℃ / min –1 ; the holding time is 0-240min (0 means that the material can be formed even if the heating process is not holding, such as the corresponding material can be formed in the heating process at a higher temperature of 1000℃), preferably 60min.
[0018] Further, the selected non-gaseous carbon source in the low temperature zone in step S3 is a liquid organic matter with relatively low boiling point (such as methyl methacrylate MMA, methanol, etc.), or a solid organic matter with relatively low decomposition temperature (such as polymethyl methacrylate PMMA, etc.).
[0019] The temperature of the low temperature zone corresponds to the boiling point temperature of the liquid organic matter ±60℃, or corresponds to the decomposition temperature of the solid organic matter ±60℃.
[0020] Further, in the S3 step, when MMA is selected as the low-temperature zone, the working temperature of the low-temperature zone is not less than 70°C, preferably 70-150°C, the temperature rising rate is 1-20°C / min –1 , and the holding time is 10-240 min.
[0021] Further, in the S3 step, when methanol is selected as the low-temperature zone, the working temperature of the low-temperature zone should be not less than 30°C, generally 30-70°C, the temperature rising rate is 1-10°C / min –1 , and the holding time is 10-200 min.
[0022] Further, in the S3 step, the inert carrier gas is specifically: inert gas such as nitrogen or argon, the gas flow rate is 1-500 sccm, and the pressure is not limited.
[0023] In the S3 step, along the axial direction of the tube furnace and the flow direction of the inert carrier gas, the low-temperature zone is located upstream of the high-temperature zone, and both temperature zones are equipped with independent heating systems for separate control and heating.
[0024] In addition, if necessary, the metal components in the nanocarbon fiber material can be selectively etched by using a corrosive agent such as an acidic solution, so that they are easily removed to finally obtain pure nanocarbon fibers.
[0025] The preparation method provided by the present application has the following beneficial effects:
[0026] The nanocarbon fiber material preparation method provided by the present application is significantly different from traditional technology in terms of innovation and efficiency. By using cost-effective carbon sources such as methyl methacrylate or methanol, and combining a simplified operation process, this method can produce homogeneous and high-curvature nanocarbon fibers at a lower temperature while reducing energy consumption and production costs. This material, due to its small and uniform size, exhibits excellent performance and is suitable for use in energy storage, catalysis, composite materials, and biomedical applications. In addition, the environmental friendliness of this method, as well as the ability to remove metal components by using an acidic agent to obtain pure nanocarbon fibers, further expands the application range of the material, showing broad market potential and development prospects. BRIEF DESCRIPTION OF DRAWINGS
[0027] In order to more intuitively demonstrate the embodiments of the present application and their technical solutions, the following will briefly introduce the accompanying charts. These charts are visual representations of the embodiments of the present application, and for those skilled in the art, they provide intuitive understanding without additional creative work. Obviously, these charts are only exemplary, and related technicians can further deduce other charts from these examples.
[0028] Figure 1is a Raman spectrum of the nanocarbon fiber material prepared in Example 1-3;
[0029] Figure 2 is a scanning electron microscope (SEM) image of the nanocarbon fiber material prepared in Example 1-3: (a), (b) Example 1; (c), (d) Example 2; (e), (f) Example 3;
[0030] Figure 3 is a transmission electron microscope (TEM) image of the nanocarbon fiber material prepared in Example 1-3: (a), (b) Example 1; (c), (d) Example 2; (e), (f) Example 3.
[0031] Figure 4 is a yield graph (based on the amount of raw material used in the high-temperature zone) of the nanocarbon fiber material prepared in Example 1-3. DETAILED DESCRIPTION
[0032] The present application is further illustrated by the following examples, which are not intended to limit the best mode contemplated, nor are they intended to limit the application to the specific examples set forth. Any person skilled in the art who has access to this application will be enabled to make and use the application, and any products or processes that are the same as or similar to the present application that are made or performed by any person who has access to this application, either as a result of the present application or by combining the present application with other prior art, are within the scope of the present application.
[0033] The specific operation methods and test methods used in the present application are conventional methods in the art, and if not otherwise specified, the conventional experimental operations or conditions described in the literature in the art can be used. The reagents involved in the present application are all conventional commercially available products.
[0034] Example 1
[0035] The present application provides a homogeneous high-curvature porous nanocarbon fiber material and an efficient carrier-free preparation technology thereof, which comprises the following steps:
[0036] S1. Citric acid and Ni(NO3)2·6H2O are weighed and dissolved in deionized water to prepare a precursor solution, the concentration of citric acid in the precursor solution is 1 mol / L –1 , and the concentration of Ni(NO3)2·6H2O is 2 mol / L –1 ;
[0037] S2. PMMA microsphere templates are added to the precursor solution, and after being immersed for 4 h, the precursor is obtained by vacuum filtration and natural drying;
[0038] S3, the MMA liquid carbon source and the precursor of S2 are respectively placed in the low-temperature section and the high-temperature section of a tube furnace, and calcination is carried out under the condition of normal pressure and 50 sccm nitrogen atmosphere. The temperature of the low-temperature section is 300 DEG C and the temperature of the high-temperature section is 600 DEG C, and the holding time is 120 min. After the calcination is completed, the temperature is decreased to room temperature, and the target nanometer carbon fiber material is obtained.
[0039] Example 2
[0040] The application provides a homogeneous high-curvature porous nanometer carbon fiber material and an efficient carrier-free preparation technology thereof, and comprises the following steps.
[0041] S1, citric acid and Ni(NO3)2.6H2O are weighed and dissolved in deionized water, and fully stirred to serve as a precursor solution. The concentration of citric acid in the precursor solution is 1 mol / L, and the concentration of Ni(NO3)2.6H2O is 2 mol / L. –1 –1 ;
[0042] S2, PMMA microsphere templates are weighed and added to the precursor solution, and after being immersed for 4 hours, vacuum filtration and natural drying are carried out to obtain a precursor.
[0043] S3, the MMA liquid carbon source and the product after calcination of the precursor of S2 at 300 DEG C in an inert atmosphere are respectively placed in the low-temperature section and the high-temperature section of a tube furnace, and calcination is carried out under the condition of normal pressure and 50 sccm nitrogen atmosphere. The temperature of the low-temperature section is 300 DEG C and the temperature of the high-temperature section is 600 DEG C, and the holding time is 120 min. After the calcination is completed, the temperature is decreased to room temperature, and the target nanometer carbon fiber material is obtained.
[0044] Example 3
[0045] The application provides a homogeneous high-curvature porous nanometer carbon fiber material and an efficient carrier-free preparation technology thereof, and comprises the following steps.
[0046] S1, citric acid and Ni(NO3)2.6H2O are weighed and dissolved in deionized water, and fully stirred to serve as a precursor solution. The concentration of citric acid in the precursor solution is 1 mol / L, and the concentration of Ni(NO3)2.6H2O is 2 mol / L. –1 –1 ;
[0047] S2, PMMA microsphere templates are weighed and added to the precursor solution, and after being immersed for 4 hours, vacuum filtration and natural drying are carried out to obtain a precursor.
[0048] S3, the product of calcination of the methanol liquid carbon source and the product of calcination of the S2 precursor at 300°C in an inert atmosphere were placed in the low-temperature section and the high-temperature section of a tube furnace, respectively, and calcined under normal pressure in a nitrogen atmosphere of 50 sccm. The temperature of the low-temperature section was 70°C for 120 min, and the high-temperature section was calcined at 600°C for 120 min. Subsequently, natural cooling to room temperature was performed, and a nanocarbon fiber material was obtained.
[0049] Test Example 1
[0050] The nanocarbon fiber material obtained was measured for physical properties such as morphology and chemical components using a Regulus 4800 scanning electron microscope (SEM), a JEM F200 high-resolution electron transmission microscope (TEM), and a LabRam HR Evolution Raman spectrometer.
[0051] Obviously, the above examples are only used to help understand the method of the present application and its core idea, and are not a limitation on the embodiments. It should be noted that, for those skilled in the art, other different forms of changes or variations can be made without departing from the principles of the present application, and these are still within the protection scope of the claims of the present application.
Claims
1. A homogenously high-curvature porous nanocarbon fiber material, characterized by, A new type of nanocarbon fiber material with uniform diameter, high curvature and uniform nanoporous structure, i.e. the whole material is a porous material formed by or including nanocarbon fibers with uniform diameter and high curvature, the porosity is formed between the fibers with high curvature, i.e. curved fibers, and the nanocarbon fibers have the crystal structure characteristics of "fishbone".
2. The method of claim 1, wherein the homogeneous high-curvature porous nanocarbon fiber material is prepared by the steps of: The method comprises the following steps: S1, citric acid and nickel nitrate are mixed into an aqueous solution according to a certain concentration ratio, and the mixture is fully stirred as a precursor solution; S2, the polymethyl methacrylate (PMMA) microsphere template is fully immersed in the precursor solution obtained in S1, and the precursor is obtained after filtration and drying; S3, the precursor obtained in step S2 or / and its derivative calcined in an inert atmosphere is placed in a high-temperature zone, and a selected non-gaseous carbon source is placed in a low-temperature zone, then under the protection of an inert carrier gas, the carbon source in the low-temperature zone is gasified and flows to the high-temperature zone with the inert carrier gas, and the decomposition product in the high-temperature zone is catalytically converted into nanocarbon fibers by the in-situ generated catalyst, and the target nanocarbon fiber material is obtained in the high-temperature zone after cooling to room temperature.
3. The method of claim 2, wherein, The concentration of citric acid in the precursor solution is 0.5-2 mol / L –1 ; preferably, the concentration of citric acid in the precursor solution is 1.0 mol / L –1 ; The concentration of nickel nitrate in the precursor solution is 0.5–3 mol L –1 Preferably, the concentration of nickel nitrate in the precursor solution is 2 mol L –1 .
4. The method of claim 2, wherein, The immersion condition is that the immersion time at room temperature should be no less than 4 hours; preferably, the immersion condition is that the immersion time at room temperature is 12 hours.
5. The method of claim 2, wherein, The precursor obtained in S2 or / and the derivative obtained by directly calcining the precursor obtained in S2 at 290-400℃ in an inert atmosphere is placed in the high-temperature zone in the S3 step. The calcination temperature in the high-temperature zone in the S3 step is not less than 380℃, preferably 450-1000℃, and the holding time is 0-240min, preferably 60min.
6. The method of claim 5, wherein, The temperature increase rate in the high temperature zone is 1 - 50 °C min –1 , preferably 10 °C min –1 .
7. The method of claim 2, wherein, The selected non-gaseous carbon source in the low-temperature zone is a liquid organic material with a relatively low boiling point or a solid organic material with a relatively low decomposition temperature; The temperature of the low-temperature zone corresponds to the boiling point temperature of the liquid organic material within ±60℃, or corresponds to the decomposition temperature of the solid organic material within ±60℃.
8. The method of claim 2, wherein, The selected non-gaseous carbon source in the low-temperature zone is a liquid organic material with a relatively low boiling point selected from methyl methacrylate MMA, methanol, or a solid organic material with a relatively low decomposition temperature, i.e. polymethyl methacrylate PMMA.
9. The method of claim 8, wherein, The working temperature of the low-temperature zone in the S3 step is not lower than 70°C, preferably 70-150°C, and the temperature rising rate is 1-20°C / min –1 , and the holding time is 10-240 min. The working temperature of the low temperature zone in the S3 step should be not lower than 30℃, generally 30-70℃, the temperature rising rate is 1-10℃ / min –1 , and the holding time is 10-200 min.
10. The method of claim 2, wherein, The inert carrier gas in the S3 step is specifically an inert atmosphere such as nitrogen or argon, and the gas flow rate is 1-500sccm, and the pressure is not limited; Along the axial direction of the tube furnace and the direction of the inert carrier gas flow, the low-temperature zone is located upstream of the high-temperature zone, and both temperature zones are equipped with independent heating systems.
Citation Information
Cited By
A carbonaceous honeycomb-structured few-walled carbon nanotube material and a controllable preparation method thereof
CN122667560A